Elevated Aggression and Reduced White Matter Integrity in Mild Traumatic Brain Injury: A DTI Study - Dailey, Natalie S.; Smith, Ryan; Bajaj, Sahil; Alkozei, Anna; Gottschlich, Melissa K.; Raikes, Adam C.; Satterfield, Brieann C.; Killgore, William D. S. (Frontiers in Behavioral Neuroscience, 2018)
Mild traumatic brain injury (mTBI) remains the most commonly reported head injury in the United States, and is associated with a wide range of post-concussive symptoms including physical, cognitive, and affective impairments. Elevated aggression has been documented in mTBI; however, the neural mechanisms associated with aggression at the chronic stage of recovery remain poorly understood. In the present study, we investigated the association between white matter integrity and aggression in mTBI using diffusion tensor imaging (DTI). Twenty-six age-matched adults participated in the study, including 16 healthy controls and 10 individuals in the chronic stage of recovery (either 6-months or 12 months post-mTBI). Psychological measures of aggression included the Buss-Perry Aggression Questionnaire and the Personality Assessment Inventory. Axonal pathways implicated in affective processing were studied, including the corpus callosum, anterior thalamic radiation, cingulum, and uncinate fasciculus, and measures of white matter integrity included fractional anisotropy, mean diffusivity, radial diffusivity, and axial diffusivity. We found that adults with mTBI in the chronic stage of recovery had higher levels aggression. Individuals with mTBI also had greater radial diffusivity in the corpus callosum compared to healthy controls, indicating reduced fiber integrity. Furthermore, we observed a significant association between reduced white matter integrity in the corpus callosum and greater aggression. Our findings provide additional evidence for underlying neuroanatomical mechanisms of aggression, although future research will be necessary to characterize the specific relationship between aggression and the white matter pathways we identified.